Imaging the kidney: from light to super-resolution microscopy. Issue 1 (19th July 2019) - Angelotti, Maria Lucia; Antonelli, Giulia; Conte, Carolina; Romagnani, Paola
Abstract: The important achievements in kidney physiological and pathophysiological mechanisms can largely be ascribed to progress in the technology of microscopy. Much of what we know about the architecture of the kidney is based on the fundamental descriptions of anatomic microscopists using light microscopy and later by ultrastructural analysis provided by electron microscopy. These two techniques were used for the first classification systems of kidney diseases and for their constant updates. More recently, a series of novel imaging techniques added the analysis in further dimensions of time and space. Confocal microscopy allowed us to sequentially visualize optical sections along the z -axis and the availability of specific analysis software provided a three-dimensional rendering of thicker tissue specimens. Multiphoton microscopy permitted us to simultaneously investigate kidney function and structure in real time. Fluorescence-lifetime imaging microscopy allowed to study the spatial distribution of metabolites. Super-resolution microscopy increased sensitivity and resolution up to nanoscale levels. With cryo-electron microscopy, researchers could visualize the individual biomolecules at atomic levels directly in the tissues and understand their interaction at subcellular levels. Finally, matrix-assisted laser desorption/ionization imaging mass spectrometry permitted the measuring of hundreds of different molecules at the same time on tissue sections at high resolution. This review provides an overview of available kidney imaging strategies, with a focus on the possible impact of the most recent technical improvements.